(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To review of paraclinical characteristics of pregnant women undergoing laparoscopic surgery for ovarian tumors at Hanoi Obstetrics and Gynecology Hospital. Material and methods: A cross-sectional retrospective study of over 74 pregnant women diagnosed with ovarian tumors who underwent laparoscopic surgical intervention at Hanoi Obstetrics and Gynecology Hospital from January 1, 2019 to December 31, 2023. Results: The average age of pregnant women diagnosed with ovarian tumors in the study was 27.1 ± 4.0, often found in employees. The most common complaint of patients admitted to the hospital is pain in the lower abdomen with 74.3%. The most common gestational age when detected is ≤ 12 weeks of age with the highest rate being 79.7% and up to 67.6% of pregnant women require surgery during pregnancy at this age. Most of the study subjects had unilateral ovarian tumors (89.2%) according to endoscopic diagnosis. The proportion of ovarian tumors measuring 10 cm or less accounts for 56.8%, the proportion of ovarian tumors over 10 cm accounts for 43.2%. According to the O-RADS classification, the main group is O-RADS2, accounting for 58.1%, followed by O-RADS3 with a ratio of 35.1%. Most cases were detected with tumor twisting (70.3%) with the rate of 1 turn, 2 turns and 3 turns of tumors twisting being 14.9% respectively; 39.2% and 16.2%. Conclusion: Research results show that the 20-35 age group is the most common group. In recent years, laparoscopy has made significant progress thanks to the development of modern endoscopic equipment and the improvement of surgeons’ skills. These improvements have facilitated the performance of laparoscopic surgery for large cervical tumors, even with pregnancy. Although most cysts in pregnant women in our study were 10 cm or less in size. This shows that laparoscopic surgery can be successfully applied to cases of large ovarian tumors, but it needs to be prepared and carried out carefully, ensuring safety for both mother and fetus. In general, with advances in laparoscopic surgical techniques and modern equipment, the ability to operate on larger ovarian tumors has increased, opening up more treatment opportunities for more complex cases.